Periodic hypersomnia, congenital ectodermal disorders and multiple exostosis - Rubens Reimão; Aron Diament (Arquivos de Neuro-Psiquiatria)
A case of periodic hypersomnia in an 11-year-old female with the unique features of mental deficiency, incontinentia pigmenti, acanthosis nigricans and hereditary multiple exostosis (diaphysial aclasis) is reported. The clinical, Polysomnographic and Multiple Sleep Latency test features of this case with a follow up of seven years are consistent with a diagnosis of periodic (intermittent) excessive somnolence. The unique presentation, however, does differ from Kleine-Levin syndrome and suggests a relationship between the predominantly ectodermal, congenital disorders and the sleep-wake, pattern dysfunction.